2010
DOI: 10.5194/hess-14-1581-2010
|View full text |Cite
|
Sign up to set email alerts
|

Changes in flood frequencies in Switzerland since 1500

Abstract: In northern Switzerland, an accumulation of large flood events has occurred since the 1970s, preceded by a prolonged period with few floods (Schmocker-Fackel and Naef, 2010). How have Swiss flood frequencies changed over the past 500 years? And how does the recent increase in flood frequencies compare with other periods in this half millennium? We collected historical flood data for 14 Swiss catchments dating back to 1500 AC. All catchments experienced marked fluctuations in flood frequencies, and we were able… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 46 publications
9
70
0
Order By: Relevance
“…For example, both Brázdil et al (1999) and Schmocker-Fackel and Naef (2010) found few floods in northern Switzerland in the first half of the 16th century but there was a flood frequency peak in 1560-1590, whereas a first peak in Sweden is found only in the following 2 decades. As for the 17th century, there was a low in Switzer-land until the first decades of the 18th century (Pfister, 1999;Schmocker-Fackel and Naef, 2010). The latter half of the century was again a period of high frequency, which only partially coincides with the documentary data from Sweden.…”
Section: Comparison With Flood-rich and Flood-poor Periods In Continementioning
confidence: 96%
See 2 more Smart Citations
“…For example, both Brázdil et al (1999) and Schmocker-Fackel and Naef (2010) found few floods in northern Switzerland in the first half of the 16th century but there was a flood frequency peak in 1560-1590, whereas a first peak in Sweden is found only in the following 2 decades. As for the 17th century, there was a low in Switzer-land until the first decades of the 18th century (Pfister, 1999;Schmocker-Fackel and Naef, 2010). The latter half of the century was again a period of high frequency, which only partially coincides with the documentary data from Sweden.…”
Section: Comparison With Flood-rich and Flood-poor Periods In Continementioning
confidence: 96%
“…Wetter et al, 2011;Benito et al, 2003;Glaser et al, 2010;Glaser and Stangl, 2004;Elleder, 2013;De Kraker, 2006). For example, both Brázdil et al (1999) and Schmocker-Fackel and Naef (2010) found few floods in northern Switzerland in the first half of the 16th century but there was a flood frequency peak in 1560-1590, whereas a first peak in Sweden is found only in the following 2 decades. As for the 17th century, there was a low in Switzer-land until the first decades of the 18th century (Pfister, 1999;Schmocker-Fackel and Naef, 2010).…”
Section: Comparison With Flood-rich and Flood-poor Periods In Continementioning
confidence: 97%
See 1 more Smart Citation
“…Synchronization is a widespread phenomenon that can be observed in numerous climate-related processes, such as synchronized climate changes in the northern and southern polar regions (Rial, 2012), see-saw relationships between monsoon systems (Eroglu et al, 2016), or coherent fluctuations in flood activity across regions (Schmocker-Fackel and Naef, 2010) and among El Niño and the Indian summer monsoon (Maraun and Kurths, 2005;Mokhov et al, 2011). Synchronous occurrences of climate-related events can be of great societal relevance.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has two main purposes: (a) to obtain data concerning rivers or torrents that lack instrumental data; and (b) to expand the observation period of instrumented rivers to the pre-measurement epoch, to improve the assessment of flood recurrence and trend Herget and Meurs, 2010;Schmocker-Fackel and Naef, 2010). In cases where the river flow is extremely variable, discontinuous or sporadic, as widely observed in many Mediterranean areas and other world regions, the time series of river discharge yield or water height are generally unavailable for long periods and/or large areas.…”
Section: Introductionmentioning
confidence: 99%